From Plant Nursery to Field: Persistence of Mycorrhizal Symbiosis Balancing Effects on Growth-Defence Tradeoffs Mediated by Rootstock - Luca Nerva; Raffaella Balestrini; Walter Chitarra (Agronomy, 2023)
The plant domestication process led to crops with strongly modified growth-defense tradeoff features, and crops that were much more pampered in terms of nutrition, irrigation and defense measures, showing less ability to trigger adaptation strategies with respect to their wild relatives. It is worth noting that plants are not alone, they share their environment with a myriad of microbes supporting them with many relevant functions. We have already demonstrated that an arbuscular mycorrhizal fungal (AMF) inoculum (formed by two AMF species, i.e., Rhizophagus irregularis and Funneliformis mosseae) is able to balance growth and defense responses in two grapevine rootstocks with opposite tradeoff features. In the present study, we evaluated the persistence of AMF-mediated balancing effects under field conditions, confirming the positive impact of the symbiosis in vineyards. In detail, some genes related to nitrogen (N) uptake and metabolism were specifically modulated by the presence of the symbionts, while others were not. Additionally, photosynthetic performances and stilbenes accumulation were influenced by the AMF presence. Overall, our results open new questions about the timing of AMF inoculation in grapevine to obtain a stable and functional symbiosis, suggesting that an early inoculation can facilitate the interaction between grapevine roots and these beneficial microorganisms.